THE EVALUATION OF THREE DIFFERENT COMPOSITE RESINS USED FOR PERIODONTAL SPLINTS: AN ULTRAMORFOLOGICAL ANALYSIS - Ionut Luchian; Darius Sandu; Magda Antohe; Maria-Alexandra Martu; Ancuta Goriuc; Giorgio Nichitean; Ioana Martu; Iustin Tapu; Dana-Gabriela Budală; Diana Diaconu-Popa; Monica-Silvia Tatarciuc (Romanian Society of Oral Rehabilitation, 2023)
The purpose of this study was to evaluate the characteristics of three types of composite resins used for periodontal immobilization systems' realization, the G-aenial Flo X (GC Corporator-Tokyo, Japan), the GrandioSO (VOCO-Cuxhawen, Germany), and the Clearfil Majesty ES flow (Kuraray Noritake Dental Inc.-Okayama, Japan). The structural analyses were realized by scanning electron microscopy, using a QUANTA 200 3D scanning electronic microscope (FEI, Netherlands), and the determination of the elemental composition of the materials was realized via X-ray spectroscopy with energy dispersion (EDX). The results showed that the GrandioSO composite demonstrated the most resistant nonporous structure, due to the presence of a homogeneous matrix characterized by low proportions of silicon and carbon. Further research is required in order to analyze the mechanical parameters of these resins and their behavior in different biological environments, in vitro and in vivo.